Pengaruh Model Pembelajaran Problem Based Learning Berbasis HOTS Pada Pembelajaran IPAS Kelas IV di SD Negeri 02 Gawanan Tahun Pelajaran 2022/2023 - Annas Kurnia Sari; Oktiana Handini; Sarafuddin Sarafuddin (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the increase in the value of the eye science lessons material ethnic and cultural diversity in Indonesia with using the HOTS-based Problem Based Learning, learning model at fourth grade students at SD Negeri 02 Gawanan, Colomadu District Lesson 2022/2023. This research was conducted at SD Negeri 02 Gawanan Colomadu. Subject In this study, there were 22 students in class IV, consisting of 22 students. This research carried out in 4 stages, namely, try out (trial), pre-test, treatment, post-test.Treatment was given in 2 stages. Data analysis techniques used descriptive comparative that is by comparing the value of pre-test and post-test. Data processing techniques use the prerequisite test and Paired test Sample T-Test. Based on the calculation of the hypothesis test, the value of tcount = 5.005 is obtained. Level at 5% significance. So it can be concluded, there is a difference between learning outcomes IPAs before and after being given the Effect of Problem Based Learning Models HOTS based.